Role of Toll-like receptor 2 during infection of Leptospira spp: A systematic review. - Chamila Kappagoda; Indika Senavirathna; Thilini Agampodi; Suneth Buddhika Agampodi (PLoS ONE)
The involvement of Toll-like receptor 2 (TLR2) in leptospirosis is poorly understood. Our systematic review examined its role across in-vitro, in-vivo, ex-vivo, and human studies. Original articles published in English up to January 2024, exploring the role of TLR2 during leptospirosis, were selected from databases including PubMed, Web of Science, Scopus, Trip, and Google Scholar. Cochrane guidelines and Preferred Reporting Items for Systematic Reviews and Meta-Analyses were followed by this systematic review. The National Institute of Health Quality Assessment tool, Systematic Review Centre for Laboratory Animal Experimentation risk of bias tool, and Office of Health Assessment and Translation extended tool were used to assess the risk of bias of the studies. Out of 2458 studies retrieved, 35 were selected for the systematic review. These comprised 3 human, 17 in-vitro, 5 in-vivo, 3 ex-vivo, and 7 studies with combined experimental models. We assessed the direct TLR2 expression and indirect TLR2 involvement via the secretion/mRNA expression of immune effectors during leptospirosis. Notably, we observed the secretion/mRNA expression of several cytokines (IL6, IL8, IL-1β, TNFα, IFNγ, IL10, CCL2/MCP-1, CCL10, COX2, CXCL1/KC, CXCL2/MIP2) and immune effectors (hBD2, iNOS, Fibronectin, Oxygen, and Nitrogen reactive species) as key aspects of host TLR2 responses during leptospirosis. Even though increased TLR2 expression in in-vivo and in-vitro studies was evident, human studies reported mixed results showing that the postulated effect of TLR2 response based on other studies may not be valid for human leptospirosis. Besides the role of TLR2 in response to leptospirosis, the involvement of TLR4 and TLR5 was identified in in-vitro and in-vivo studies. TLR2 expression is inconclusive during human leptospirosis and further studies are needed to examine the immune effector regulation, through TLR2 for mitigating the harmful effects and promoting effective immune responses.